Neoadjuvant Chemotherapy versus Chemoradiation Prior to Esophagectomy: Impact on Rate of Complete Pathologic Response and Survival in Esophageal Cancer Patients. Issue 12 (December 2016) - Samson, Pamela; Robinson, Clifford; Bradley, Jeffrey; Lockhart, Craig A.; Puri, Varun; Broderick, Stephen; Kreisel, Daniel; Krupnick, Sasha A.; Patterson, Alexander G.; Meyers, Bryan; Crabtree, Traves
ABSTRACT : Objectives: : The aim of this study was to evaluate differences in pathologic complete response (pCR) rates and overall survival among patients receiving either neoadjuvant chemotherapy or chemoradiation before esophagectomy for locally advanced esophageal cancer. Methods: : Patients with esophageal cancer receiving either neoadjuvant chemotherapy or chemoradiation before esophagectomy were identified using the National Cancer Database. Univariate analysis compared patient, tumor, and postoperative outcome characteristics. Logistic regression was performed to identify variables associated with achieving pCR. Kaplan‐Meier analysis was performed to compare overall median survival by neoadjuvant therapy type and pCR status. Finally, a Cox proportional hazards model was fitted to identify variables associated with increased mortality hazard. Results: : From 2006 to 2012, a total of 916 of 7338 of patients (12.5%) received neoadjuvant chemotherapy whereas 6422 (87.5%) received neoadjuvant chemoradiation. Patients who received neoadjuvant chemoradiation were more likely to achieve a pCR (17.2% versus 6.4%, p < 0.001) and less likely to have positive margins (5.6% versus 11.5%, p < 0.001) than were patients who received neoadjuvant chemotherapy, with no difference in 30‐ or 90‐day mortality. Achieving a pCR was associated with improved overall median survival (59.5 ± 4.0 months versus 30.1 ± 0.76 months for those with persistent disease, p < 0.001). On logistic regression, neoadjuvant chemoradiation therapy was independently associated with achieving a pCR (OR = 2.75, 95% confidence interval: 2.01–3.77, p < 0.001). Despite improvement in the pCR rate with neoadjuvant chemoradiation, neoadjuvant therapy type was not independently associated with long‐term survival (hazard ratio = 1.12; 95% confidence interval: 0.97–1.30, p = 0.12). Conclusions: : Although neoadjuvant chemoradiation is more successful in downstaging esophageal cancer before esophagectomy, it was not independently prognostic for improved long‐term survival. Other factors affecting long‐term survival among pathologic complete responders and among patients with persistent disease should be investigated to clarify this association.